Effects Of Incorporating Shredded Waste Plastic Bottles (PET) As an Additive in A Bituminous Mixture - Kiptoo , Koech Amos; Kiptoo , Koech Amos; Simpson Nyambane, Dr. Eng. Osano; Mumenya, Prof. Siphila Wanjiku (African Journal of Education,Science and Technology (AJEST), 2024)
Asphalt has been in use for decades and its significance as an important engineering material cannot be overstated. In the last few decades, modification of asphalt/bitumen mixtures using polymers has attracted a lot of worldwide interest based on the numerous advantages it possesses. Polymer modified bitumen (PMB) appears to have substantial potential for its effective application in the design of flexible pavements to improve their effective service life. Pavements made with PMB have proven to offer relatively better resistance towards permanent deformation, rainwater, reduction in potholes and stripping as well as stronger roads with greater rigidity and increased Marshall stability. Nonetheless, polymer-modified bituminous mixtures are relatively more costly for a road pavement. A way of cutting on construction expenses is the utilization of less expensive polymers such as waste polymers. Not only is the recycling of waste materials beneficial to the environment, but it also has the potential to enhance the performance of flexible pavements and be cost-effective. It is because of the aforementioned reasons that this research identified the potential for use of waste polymer that is readily available, in form of waste plastic bottles (Polyethylene Terephthalate - PET), in construction of pavements across Kenya. This research’s primary purpose is to evaluate the effect of the incorporation of shredded waste plastic bottles (PET) as a modifier on the engineering and volume properties of a bituminous mix. To accomplish this, a reference mix, (containing 0% PET additive) was prepared and the Marshall test was performed on this sample to obtain the optimum bitumen-binder content. Once the optimum bitumen content was obtained, waste Plastic bottles were shredded to small pieces. For ease of incorporation of the shredded waste plastic bottles into the asphalt mix, the research did not conduct sieve analysis of the shredded PET. Shredded PET were incorporated into the mix via the dry process through replacing the optimum bitumen content with 0%, 6%, 10%, 14% and 18% PET per weight of this optimum bitumen content. The samples obtained were then evaluated for their engineering and volume properties. The study involved the analysis of the volume properties as well as Marshall Stability and flow test. The results of the study highlighted that 6% and 10 % PET modified bituminous mix met all the criteria highlighted in Overseas Road Note 19 (ORN 19). Additionally, the aforementioned had higher stability compared to neat samples. Accordingly, it is concluded that PET modification of a bituminous is a viable and can have a positive impact on a bituminous mixture. This paper will form a basis that will not only assist Engineers in better understanding the effects of incorporating shredded waste PET into a bituminous mix on a pavement’s engineering properties, but can also assist the Kenyan government with its environmental conservation efforts through providing an alternative for the use of waste plastic bottles.